Implementation of narrative flows in Indonesian women’s movement Museum display area - Wulandari, A. A. A.; Jocelyn, S.; Simanjuntak, P. M. (AIP conference proceedings, 2023)
This study aimed to make the display system at the Museum Pergerakan Wanita Indonesia or Indonesian Women’s Movement Museum more interesting and inform visitors from the general public and young generation by utilizing the combined discursive and immersive narrative display method. The research method used in this research was a qualitative method for collecting secondary data and primary data. The data used was taken from general knowledge about the history of Indonesian women’s movements and primary data derived from the Indonesian Women’s Movement Museum data. The analyzed general data was then applied in the form of design in the application of the display layout system of the Indonesian Women’s Movement Museum. In this study, the subject specifically discussed was the area of the Pre-Independence Exhibition, which told about the condition of women before emancipation toward the starting point of the women’s movement began. The narrative flow in the exhibition area aims to provide informative data as well as to build the emotions of visitors to have feelings of empathy and involvement in the historical story itself.